Investigating the potential for green roofing in Nottingham, UK - Mularczyk, Ragnar (2024)
The importance of developing wide-ranging sustainable practices is gradually being more greatly appreciated and demands for implementation are growing. Green roofs have a history pre-dating the recent dawn of sustainable innovation, though they are now progressively being recognised for the sustainable benefits they can offer, including supporting biodiversity, improving building thermal insulation, and reducing stormwater runoff. Nevertheless, their uptake has been hindered by prominent barriers including cost, a persisting lack of awareness and understanding, and insufficient incentivisation. Local context can have significant influences upon the opportunities for green roofs to become widespread, including the current priorities of the local authority.